2018
DOI: 10.19082/6286
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with congenital hypothyroidism: a case-control study in southeast Iran

Abstract: Background and aimCongenital hypothyroidism (CH) is known as one of the most common preventable cause of mental retardation. This study aimed to determine factors associated with CH in Iran.MethodsThis case-control study was conducted on 160 children under one year old in Zahedan in southeast Iran in 2016. The neonates who were born from March 1, 2015 to March 19, 2016 and had undergone a screening program for CH were the study population. The neonates with serum TSH > 10mIu/L and T4 < 6.5 or TSH > 30 mIu/L we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
(32 reference statements)
1
10
0
1
Order By: Relevance
“…This study showed no significant association between birth weight and transient or permanent CH, as shown by Khammarnia et al previously [ 26 ].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This study showed no significant association between birth weight and transient or permanent CH, as shown by Khammarnia et al previously [ 26 ].…”
Section: Discussionsupporting
confidence: 64%
“…The incidence of permanent and transient CH was higher amongst neonates with short height as compared to neonates with normal height. Khammarnia and colleagues also showed similar results with a two-fold increased risk of CH among children with short height than those with normal height [ 26 ].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Several studies indicated that CH was considered as one of the most common preventable causes of mental retardation [28]. Certain irreversible complications for infants, such as neurological damage, slow growth, delayed skeletal maturation and mental retardation might be caused in case of untimely treatment of CH [2932]. Therefore, the exploration of additional CH risk factors, such as air pollution plays a crucial role in reducing the incidence of CH and improving the quality of life in the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…These studies investigated some risk factors of CH such as the type of delivery; weight, length, and head circumference at birth; iodine deficiency; mother's; birth season; sex; and postdate delivery. [ 1 9 10 11 12 13 14 ]…”
Section: Introductionmentioning
confidence: 99%